สภาพและปัญหาการบริหารสิ่งแวดล้อมที่ปลอดภัยในโรงเรียนประถมศึกษา สังกัดกรุงเทพมหานคร - รุ่งนภา สง่าแสง (จุฬาลงกรณ์มหาวิทยาลัย, 2002)
The purposes of the research were to study the state and administrative problems and compare the administrative problems on safety environment of different school sizes under the Jurisdiction of Bangkok Metropo is.Questionnaires were sent to 862 respondents and 720 questionnaires, accounted for 83.52 percent, were returned. The data were then analyzed by means of percentages, means, and standard deviations. One-way analysis of variance and Scheffe test were also applied to test the significant differences ai .05 level. The findings were as follows: 1. Most schools had safety environment but most schools had over three stones with no emergency doors or ore ladder exits. Characteristic of accidents found were bumping, falling, and sport injuries. Most accidents occurred in the fields, play grounds and school buildings. 2. The safety environment administrative problems were at the "moderate" level. The problems on the management, man and money were also found at the ‘moderate" level with the exception of problems regarding places and buildings which were at the "low" level. 3. Comparing the administrative problems on safety environment among those from the large. medium and small size schools revealed the statistically significant differences at the .05 level. The large and medium size schools had more problems than small size schools. The place and building had statistically significant differences at .05 level.